Does graduate economics education address the cognitive challenges of effective teaching?. Issue 1 (2nd January 2021) - Stock, Wendy A.
Abstract: What do we know about how well graduate teaching in economics addresses cognitive challenges to learning? In short, very little. There is a dearth of research that investigates how graduate student, program and professor characteristics, and choices impact graduate student learning and other outcomes. Some of the broader literature on graduate education in economics includes findings that can be linked to Chew and Cerbin's cognitive challenges to provide suggestive evidence, but many open research questions remain. Research is needed to understand whether improvements like clear communication, clear requirements and expectations, better advising, and adopting a learning-driven approach to graduate courses would mitigate cognitive challenges to learning and improve graduate education in economics.